2002
DOI: 10.1016/s0014-5793(02)03804-8
|View full text |Cite
|
Sign up to set email alerts
|

Normal function of HERG K+ channels expressed in HEK293 cells requires basal protein kinase B activity

Abstract: The potential role of protein kinase B (PKB), a serine/threonine protein kinase, in regulating HERG (human ethera-go-go related gene) K + channel function was investigated. Wortmannin (a phosphoinositide 3-kinase (PI3K) inhibitor) caused V V30% reduction of HERG current (I HERG ) stably expressed in HEK293 cells. Transient transfection with the constitutively active PI3K in HERG-expressing HEK293 cells slightly increased (V V7%) I HERG while a dominant negative PI3K signi¢cantly reduced I HERG (V V25%) relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 35 publications
4
44
1
Order By: Relevance
“…See Discussion for further details. density in stably expressing HEK cells (Zhang et al, 2003), though the underlying mechanism was not elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…See Discussion for further details. density in stably expressing HEK cells (Zhang et al, 2003), though the underlying mechanism was not elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly TNF-␣, which can induce sphingomyelinase activation and ceramide production, was recently shown to reduce the HERG current via reactive oxygen species (ROS) . In addition to ROS, ceramide signalling also results in activation of protein kinase C and alteration of protein kinase B activity (Ruvolo, 2001;Ramström et al, 2004) both of which modulate HERG channel function (Barros et al, 1998;Thomas et al, 2003;Zhang et al, 2003). However, little is known of the effects of ceramide on…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified major roles of Akt/PKB in cell proliferation and survival and in insulin signaling (5,32). Although information regarding role of Akt/PKB in activation of ion channels is sparse (2,56), Akt/PKB was activated during hypotonic swelling of PASMCs (Fig. 6B) and hence was considered a potential regulatory protein upstream of VSOACs.…”
Section: Discussionmentioning
confidence: 99%
“…These observations independently confirmed that hypotonic swelling of PASMCs activates PI3Ks and downstream kinases, including Akt/PKB. Akt/PKB has been shown to modulate L-type Ca 2ϩ (2) and human ether-a-go-go-related gene potassium channels (56). To test whether Akt/PKB is involved in activation of VSOACs, we dialyzed through the patch pipette recombinant active Akt1 (20 U/ml) into cultured PASMCs.…”
Section: Hypotonic Activation Of Pi3k Leads To Activation Of Akt/ Pkbmentioning
confidence: 99%
“…APC Min/ þ animals show overexpression of several members of the Eag family of Kv channels, as well as of BK channels. Erg channels are activated by Akt (Zhang et al, 2003) and confer greater malignancy to patients with leukemia (Pillozzi et al, 2007). Moreover, mutations in the APC gene alter cell cycling (Dikovskaya et al, 2007), and as Eag family channels are cell cycle regulated (Wonderlin and Strobl, 1996), it is likely that these changes affect their activity.…”
mentioning
confidence: 99%